Barriers to people's participation in watershed intervention projects: perspectives of experts and local communities - Noor, Hamzeh; Tabe, Marzieh; Salehpour Jam, Amin; Khaleghi, Bagher (Aqua (London, England), 2024)
The present study aimed to identify and prioritize people's participation barriers (PPBs) in watershed intervention projects (WIPs), considering the perspectives of both experts and local people in the Dastgerd watershed, Iran. Thirteen important PPBs in the implementation of WIPs were identified in the study. The findings indicated that a lack of participatory guidelines, an expert-oriented decision-making process, and a deficiency in economic incentives during the implementation of WIPs constituted the most crucial PPBs. In addition, according to the two-sample KS test, there is a significant difference in the perspectives of the two groups regarding the importance of 60% of PPBs. The biggest differences were observed concerning the two barriers of `ignoring people's benefit from the project' and `lack of people consultation and attention to their suggestions'. Given the substantial impact of expert opinions on policy-making in watersheds, any misconceptions they hold regarding barriers and incentives for people's participation can lead to adverse outcomes in the planning of soil and water conservation projects. To address this issue, the establishment of think tanks and the facilitation of brainstorming sessions play a pivotal role in fostering mutual understanding, aligning the perspectives of local people and experts, and making informed decisions to overcome challenges.